Energy-Exergy Analysis of A Novel Multi-Pass Solar Air Collector With Perforated Fins - Aktaş, Mustafa; Sözen, Adnan; Tuncer, Azim Doğuş; Arslan, Erhan; Koşan, Meltem; Çürük, Osman (Center of Biomass & Renewable Energy, Diponegoro University, 2019)
This work presents performance analysis of a novel multi-pass solar air collector with perforated fins (MPSACF) in winter conditions, Ankara province, Turkey. The aim of this work is to experimentally test and compare the performance of the two different design of solar collectors in the same climatic conditions. In addition, a double-pass solar air collector without fins (DPSAC) at the same absorber area was manufactured and tested as a control group. The total absorber area of both solar collectors is 0.325 m2. Thermal effects for performance improvement of the collectors have been designated. Average thermal efficiency values of DPSAC and MPSACF were calculated as 47.85% and 51.86%, 67.10% and 72.86%, respectively in experiments performed at 0.0069 kg/s (0.7 m/s air velocity) and 0.0087 kg/s (0.9 m/s air velocity) mass flow rates. Exergy efficiency of DPSAC and MPSACF were 2.10-17.12% and 8.74-23.97%, respectively. Coefficient of performance(COP) values were ocomputed 4.63 and 4.94, 3.18 and 3.48 respectively in experiments performed at 0.0069 kg/s and 0.0087 kg/s mass flow rates. Although the MPSACF has high efficiency values, COP values are lower due to the presence of dual fans. Because of their high thermal efficiency, both collectors can be effectively practiced for applications such as preheating, space heating and ventilation, greenhouse heating and product drying©2019. CBIORE-IJRED. All rights reservedArticle History: Received May 16th 2018; Received in revised form October 16th 2018 ; Accepted January 6th 2019; Available onlineHow to Cite This Article: Aktaş, M., Sözen, A., Tuncer, A.D., Arslan, E., Koşan, M., Çürük, O. (2019) Energy-exergy analysis of a novel multi-pass solar air collector with perforated fins. International Journal of Renewable Energy Development, 8(1), 47-55.http://dx.doi.org/10.14710/ijred.8.1.47-55